Current status of maternal and child health indicators in BRAC EHC Programme areas of Bangladesh - Chowdhury, Anita Sharif; Islam, Qazi Shafayetul; Ahmed, Syed Masud (BRAC Research and Evaluation Division (RED), 2019)
Essential Health Programme (EHC) is one of many development efforts of BRAC providing an integrated package of preventive, promotive and basic curative services at a minimum cost to improve health and nutrition of the poor especially reproductive age women and children under-five. The BRAC community-based health workers: Shasthya Shebikas (SSs) and Shasthya Kormis (SKs) provide these services through fortnightly household visits. EHC started its new phase Ill in January 2011 . Therefore, a survey was done to record benchmark data on some selected indicators among·EHC upazilas in align with MDG four and MDG five. The study randomly selected 1200 mothers of under-two children from 30 EHC Upazilas. Data were collected in March 2013.The mothers in this study represented a young age group (25 years) with higher literacy rate. Seventy one per cent were currently using modern family planning (FP) method. The majority (52%) bought pill/condom from drug shop while very few (5%) reported SSs as their source of supplies. One third of the sample households reported that they were visited once in a month by the BRAC SS, while less than a quarter (22.5%) of the households had received no visits. Forty seven per cent of the mothers received ANCs four or more times, while 42 per cent received one PNC during their last pregnancy. Less than two-third of the mothers had heard about micronutrients and had insufficient knowledge of its effect on children's health and use pattern such as appropriate age to initiate and duration of use. Ninety two per cent of the children were found to have received complete immunization. The findings revealed a better status of indicators (e.g . immunization coverage, family planning, antenatal and delivery care, and infant and young child feeding practices) in EHC upazilas than that of national average. The challenge for the programme will be to sustain the current good practices and invest further effort to achieve the desired levels to reach the MDG health goals.